PENDAPATAN SEWA ASET PT KAI (PERSERO) DAERAH OPERASI 8 SURABAYA - Jannah, Miftakhul; Andarini, Sonja (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
Income from leased assets is one source of non-operating income that plays an important role in supporting the company's financial sustainability. PT Kereta Api Indonesia (Persero) Surabaya Operation Area 8 (Daop 8) utilizes fixed assets such as land, buildings, and other facilities for rent to tenants or often called debtors. This strategy aims to optimize the economic value of assets owned and create a positive contribution to the company's financial stability. This research uses a qualitative descriptive method by reviewing literature and secondary data to discuss the process of asset rental income at PT Kereta Api Indonesia (Persero) Operating Region 8 Surabaya.